Invasive lobular breast cancer: A review of pathogenesis, diagnosis, management, and future directions of early stage disease - Thomas, Mathew; Kelly, Erinn Downs; Abraham, Jame; Kruse, Megan (Seminars in oncology, 2019)
Invasive lobular carcinoma (ILC) is the second most common type of invasive breast cancer after invasive ductal carcinoma (IDC). Invasive lobular carcinoma has unique clinical, pathologic, and radiographic features which suggest that it is a distinct clinical entity; however, it is treated with the same treatment paradigms as IDC. Information regarding the specific treatment of ILC, including response to standard therapy, is sparse. Neoadjuvant treatment considerations are of great importance in this space as ILC is often found at a locally advanced stage. In this review, we summarize the classic features of ILC and the available data regarding efficacy of both endocrine therapy and chemotherapy in curative treatment of breast cancer.